Evaluating the Effectiveness of Lifestyle Interventions in Preventing Chronic Diseases: A Systematic Review - Alorayf, Abdullah Eidhah Abdullah; Alhamamah, Mohammed Abdullah Mead; Alhamamah , Saeed Abdullah Muied; Alhamamah, Hassan Ali Maed; Almasabi , Fares Mohammed; Al jamish, Yousef Abdullah Ali; Al-Aorif, Faisal Mohsen Abdullah; Allajam, Majed Mohammed Mohammed; Alsoma, Mohammed Abdullah Hussain; Al abbas, Ali mohammed hamed (Journal of Ecohumanism, 2024)
This systematic review evaluates the effectiveness of lifestyle interventions, including dietary changes, physical activity, smoking cessation, and alcohol reduction, in preventing chronic diseases such as cardiovascular disease, diabetes, and obesity. Chronic diseases pose a significant burden globally, and lifestyle interventions are increasingly recommended to reduce risk factors. A comprehensive search was conducted in databases like PubMed, Cochrane Library, and Embase, focusing on studies published in the past decade. Included studies assessed adult populations at risk of chronic diseases, using interventions targeting lifestyle modifications with measurable health outcomes. Findings indicate that dietary changes and increased physical activity significantly reduce chronic disease risk, while smoking cessation and alcohol reduction further contribute to improved health outcomes. Combination interventions generally showed the most substantial impact on preventing chronic disease. Although the evidence strongly supports lifestyle changes for disease prevention, variations in intervention type, duration, and adherence remain a limitation. Future research should explore long-term effects and implementation strategies in diverse populations. This review underscores the need for integrating effective lifestyle interventions into healthcare policies to improve public health.